Latest Developments in Normal-Pressure Glaucoma: Diagnosis, Epidemiology, Genetics, Etiology, Causes and Mechanisms to Management - Lee, Jacky W.Y. (Asia Pac J Ophthalmol (Phila), 2019)
Normal-pressure glaucoma (NPG) is part of the spectrum of the open-angle glaucomas and morphologically characterized, as any glaucoma, by a loss of neuroretinal rim parallel to an enlargement and deepening of the optic cup, and development or enlargement of parapapillary beta zone. These morphological characteristics, in addition to the therapeutic benefit of lowering the intraocular pressure (IOP), make NPG differ from vascular-induced optic neuropathy. Based on the anatomy of the optic nerve as a cerebral fascicle, the physiological counter-pressure against the IOP is the orbital cerebrospinal fluid pressure (CSFP), with both pressures forming the trans-lamina cribrosa pressure difference (TLCPD). In contrast to the IOP, the TLCPD is the true pressure exerting force on the optic nerve fibers when passing through the lamina cribrosa. As a theoretical notion, an abnormally high TLCPD due to a low CSFP, in association with a low arterial blood pressure, could therefore be involved in the pathogenesis of NPG. It fits with the finding that the reduction of the IOP (and thus indirectly of the TLCPD) is (the only proven) procedure for NPG therapy. This review additionally highlights the genetic background, diagnostic methods, and therapeutic modalities of NPG.